EFFECTIVENESS OF A STRUCTURED TRAINING PROGRAM TO DEVELOP MOTOR COORDINATION, BALANCE, AND SOCIAL INTERACTION IN INDIVIDUALS WITH AUTISM SPECTRUM DISORDER (Proximus Journal of Sports Science and Physical Education, 2024)
Autism is a disorder that causes problems with motor performance, balance, fine motor skills, balance challenges, and communication difficulties. This study sheds light on the aspect of evaluating the effectiveness of an organized training program based on play and training that aims to develop motor skills and balance and helps in developing social interaction for those with ASD .The research aimed to enhance components and try to overcome these difficulties through a comprehensive training program as the program is characterized by containing various activities that aim to develop motor coordination and work to increase muscle strength and develop social participation between individuals and thus develop their physical fitness. The study was conducted for a group of 30 individuals ranging in age from 10-16 years grouped into two categories., each includes 15 individuals, which is the intervention group and 15 individuals, the control group. The organized training program was applied for three months at a rate of two sessions per week and the duration of the session was 60 minutes. Several measures were used to evaluate motor skills, as the motor efficiency test (BOT-2) was used to measure speed, balance, and movement accuracy. The medicine ball throwing test weighing 1 kg was also used to measure strength. Muscles This test examines upper body strength by assessing the distance a child can throw a ball.